2019
DOI: 10.3389/fnagi.2019.00320
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tau Protein in Remodeling of Circadian Neuronal Circuits and Sleep

Abstract: Multiple neurological, physiological, and behavioral functions are synchronized by circadian clocks into daily rhythms. Neurodegenerative diseases such as Alzheimer’s disease and related tauopathies are associated with a decay of circadian rhythms, disruption of sleep patterns, and impaired cognitive function but the mechanisms underlying these alterations are still unclear. Traditional approaches in neurodegeneration research have focused on understanding how pathology impinges on circadian function. Since in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
6
10
0
Order By: Relevance
“…That hTau WT /CS also showed changes in the sleep pattern may be due to it not being completely able to substitute for Drosophila dTau. This is supported by the recent finding that the loss of dTau reduces sleep and increases activity (Arnes et al, 2019). Furthermore, we found that also haploinsufficiency by using a dTau knock-out-line (Burnouf et al, 2016), impaired the sleep pattern (Supplementary Figure S3C) and induced hyperactivity when tested at 5-day ( Supplementary Figure S3D).…”
Section: Htau V337m Disrupts Sleep/activity Patterns But Not Rhythmicitysupporting
confidence: 87%
“…That hTau WT /CS also showed changes in the sleep pattern may be due to it not being completely able to substitute for Drosophila dTau. This is supported by the recent finding that the loss of dTau reduces sleep and increases activity (Arnes et al, 2019). Furthermore, we found that also haploinsufficiency by using a dTau knock-out-line (Burnouf et al, 2016), impaired the sleep pattern (Supplementary Figure S3C) and induced hyperactivity when tested at 5-day ( Supplementary Figure S3D).…”
Section: Htau V337m Disrupts Sleep/activity Patterns But Not Rhythmicitysupporting
confidence: 87%
“…dTau null flies exhibit a significant reduction in the structural morphology of the s-LNv at ZT2 compared to wt, in line with the behavioural defects (increased activity and decreased sleep) displayed in the early day (Arnes et al, 2019). Furthermore, in s-LNvs, dTau shows rhythmic expression at both mRNA and protein levels, with significantly higher levels in the early morning (ZT2) than in the early night (Abruzzi et al, 2017;Arnes et al, 2019). This temporal rhythmic pattern perfectly matches with its role in modulating the structural plasticity of s-LNvs terminals (Arnes et al, 2019).…”
Section: Lnvs and Neuronal Structural Remodelingsupporting
confidence: 65%
“…At the neuronal level, dTau plays an essential role in modulating the structural plasticity of s-LNvs terminals: in wt flies the dorsal projections of s-LNvs neurons display a rhythmic remodeling, with significantly higher degree of axonal arborisation in the early day (ZT2) compared to early night (ZT14) (Fernández et al, 2008). dTau null flies exhibit a significant reduction in the structural morphology of the s-LNv at ZT2 compared to wt, in line with the behavioural defects (increased activity and decreased sleep) displayed in the early day (Arnes et al, 2019). Furthermore, in s-LNvs, dTau shows rhythmic expression at both mRNA and protein levels, with significantly higher levels in the early morning (ZT2) than in the early night (Abruzzi et al, 2017;Arnes et al, 2019).…”
Section: Lnvs and Neuronal Structural Remodelingmentioning
confidence: 69%
See 1 more Smart Citation
“…MAPT −/− mice also spend significantly less time in the open arms of elevated Z-mazes and keep to the periphery of open field arenas, indicative of increased anxiety [86]. Tau may also help to regulate circadian behaviours, with MAPT −/− mice [41] or Drosophila [8], showing major abnormalities in the sleep-wake cycle, including increased wakefulness and disruption to normal circadian activities. Sleep disturbances are commonly reported in ageing and neurodegenerative disorders [281], so understanding how tau alterations impact sleep may be clinically relevant.…”
Section: Tau Hyperactivity Anxiety and Sleepmentioning
confidence: 99%